A miniature fractal-based dual-mode dual-band microstrip bandpass filter design - Alqaisy M.; Chakrabraty C.; Ali J.; Alhawari A.R.H. (Cambridge University Press, 2023)
Bandpass filters; Defected ground structures; Filters (for fluids); Fractals; Microwave filters; Optical resonators; Circuit design and applications; Compact filter; Complementary split-ring resonator; Dual band response; Ground planes; Measured results; Microstrip band-pass filter; Microstrip ring structure; Microstrip filters